The Relationship Between Maternal Parenting Practices and Stunting Incidence Among Toddlers in the Anam Health Center Service Area - Olivera Agnes Adar; Yosef Andrian Beo; Fransiskus Xaverius Meku (Universitas Ibn Khaldun Bogor, 2026)
Stunting is a growth disorder characterized by impaired physical development caused by chronic malnutrition, inadequate nutrient intake, and repeated infections. A child is classified as stunted when the height-for-age Z-score (HAZ) is below -2 standard deviations (SD). The occurrence of stunting is influenced by various factors, including direct factors such as infectious diseases and insufficient nutritional intake, as well as indirect factors such as poor sanitation, limited food availability, and inappropriate parenting practices. This study aimed to examine the relationship between maternal parenting patterns and stunting among children aged 12–60 months in the Anam Health Center service area. A quantitative study with a cross-sectional design was conducted. The study population consisted of mothers who had children aged 12–60 months, and 76 respondents were selected as the study sample. The findings showed that most mothers practiced a democratic parenting style (60.5%), while authoritarian (21.0%) and permissive (14.4%) parenting styles were less common. Statistical analysis using the Chi-Square test produced a p-value of 0.055 (p > 0.05), indicating that there was no statistically significant relationship between maternal parenting patterns and stunting among children aged 12–60 months. In conclusion, maternal parenting patterns were not significantly associated with the incidence of stunting among children in the Anam Health Center service area.